The Impact of China’s Foreign Direct Investment on the Economic Growth of African Countries - Iskandarov, Ali; Zeynalov, Ayaz; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the impact of Chinese Foreign Direct Investment on the economic growth of African countries over the period 2002–2022. As China has emerged as Africa's largest trading partner and a significant source of FDI, understanding the implications of this engagement is critical for assessing sustainable development prospects on the continent. Employing a quantitative panel data analysis with a Random Effects Model across 54 African nations, the study examines the effects of Chinese FDI stock and flows on key macroeconomic indicators such as GDP growth, GDP per capita, manufacturing value added, and economic complexity. The findings show that while Chinese FDI is associated with a short-term negative impact on economic growth, it positively correlates with improvements in GDP per capita, suggesting benefits to individual income levels. However, Chinese FDI appears to have no significant effect on manufacturing development or economic complexity, which raises concerns about limited industrial transformation and economic diversification. The results also indicate the crucial role of institutional quality and governance in FDI’s developmental outcomes. The thesis concludes with policy recommendations for African governments to improve governance frameworks, invest in human capital, promote export diversification, and engage proactively with Chinese investors to maximize the benefits of FDI.
Vedoucí práce: Ayaz Zeynalov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses